Disease Management of Clinical Complete Responders to Neoadjuvant Chemotherapy of Muscle-Invasive Bladder Cancer: A Review of Literature - Wu, Jie; Xie, Rui-Yang; Cao, Chuan-Zhen; Shang, Bing-Qing; Shi, Hong-Zhe; Shou, Jian-Zhong (Frontiers in Oncology, 2022)
Muscle-invasive bladder cancer (MIBC) is an aggressive disease requiring active management. Neoadjuvant chemotherapy (NAC) followed by radical cystectomy (RC) is considered as the standard treatment paradigm for MIBC patients, which could result in significant perioperative mortality and morbidity, as well as the significant alteration of quality of life (QOL). Notably, multimodal bladder-preserving treatment strategies have been recommended for highly selected patients. Pathologic complete response (pCR) after NAC is a powerful prognostic indicator of survival for patients with MIBC. Clinical complete response (cCR) is then introduced as a complementary endpoint for pCR to assess disease status preoperatively. Bladder preservation strategy for patients who achieve cCR following NAC is emerging as a new treatment concept. However, the efficiency of conservative strategy remains controversial. In this review, we discuss the advantages and limitations of cCR, and the feasibility and safety of bladder preservation strategy in highly selected MIBC patients who achieve cCR following NAC. We conclude that conservative strategy can be considered as a reasonable alternative to RC in carefully selected cCR MIBC patients, leading to acceptable oncological outcomes.